(untitled) (Journal of The Colloquium for Information Systems Security Education, 2019)
This paper gives examples of security injections in computer engineering courses, including courses on hardware design. More broadly, the paper aims to show how knowledge of hardware and software implementations relate to security exploits is important for students who design computer hardware, and how knowledge of the hardware and architectural features is important for those who focus on computer security. The paper provides examples to illustrate the impact of the knowledge of underlying architectural optimizations and hardware limitations on security features and exploits. Examples of educational tools and methods for integrating security education in context in the computer engineering curriculum are also described.